Cardiac muscle tissue engineering.
Cell-based therapy has emerged as a novel approach for replacing heart muscle, which is known not to regenerate after injury such as that caused by infarction or reconstructive surgery. Two types of cell-based therapies have been employed: injection of isolated cells or the implantation of in-vitro-grown cardiac muscle tissue equivalents In the first case, several cell types - including skeletal myoblasts, cardiomyogenic cells derived from bone marrow stroma, fibroblasts, multipotent endothelial cells, and embryonic stem cells - have been directly injected into the myocardium and have shown to result in limited recovery from heart dysfunction in different animal models and humans (in the case of myoblasts). Despite the survival and differentiation of implanted cells, mechanical and electrical cell-cell contacts between graft and the host - a requirement for synchronous contractions - has only rarely been seen.
Keywords: Animal models; Cell-based therapy; Cellular differentiation; Electrical cell-cell contacts; Embryonic stem cells; Heart muscle replacement; Humans; Implanted cells survival; Mechanical cell-cell contacts; Myocardium; Recovery from heart dysfunction; Synchronous contractions